Using peer education approach to prevent HIV/AIDS on young people in Sub Sahara Africa : example the project “Yellow Reglo A” Cameroon - Ngo Ibom, Salome Clemence (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. HIV/AIDS Management))--University of Stellenbosch, 2009.